A microarray-based analysis of oocyte quality in the European clam Ruditapes decussatus - Sousa, Joana Teixeira; Milan, Massimo; Pauletto, Marianna; Bargelloni, Luca; Joaquim, Sandra; Matias, Domitilia; Matias, Ana Margarete; Quillien, Virgile; Leitao, Alexandra; Huvet, Arnaud (Aquaculture, 2015)
WOS:000355672000004 A microarray-based analysis was performed with the objective of describing genomic features of oocytes and looking for potential markers of oocyte quality in the economically important European clam, Ruditapes decussatus. Oocytes of 25 females from Ria de Aveiro, western coast of Portugal (40 degrees 42'N; 08 degrees 40'W) were selected for this study and oocyte quality was estimated by success of D-larval rate under controlled conditions, which appeared to vary from 0 to 95%. By genome-wide expression profiling with a DNA microarray, 526 probes appeared differentially expressed between two groups representing the largest and smallest value of D larval rates, named good (represented by a mean D-larval yield of 57 +/- 22%) and poor (9 +/- 5%) quality oocytes. Enrichment analysis showed "lysosome" (dre04142) as the single pathway represented in the enriched KEGG pathway terms, with 8 genes coding for putative cathepsins. Furthermore, differentially expressed genes involved in oocyte protection (DnaJ (Hsp40), Hsp70, cyclophilin B, PDI), maturation (Cam-PDE1C, PRDM9, G protein), sperm-egg interaction (PDI, G protein) and apoptosis (TNF) were also identified. From these, the apoptosis pathway was supposed to assume an important role in oocyte quality as the mRNA level of caspase 8 appeared also negatively correlated with the D-larval yield. Finally, a G-protein transcript was identified as more abundant in poor quality oocytes, which underlines the importance of release prophase I block and meiotic maturation in the oocytes of this species. This study provided new highly valuable information on genes specifically expressed by mature oocytes of R. decussatus, for further understanding of the mechanisms of early development in this species. Statement of relevance Understand the mechanisms of early development in the European clam R. decussatus.